Morphological Characteristics and Habitats of Red Seaweed Gracilaria spp. (Gracilariaceae, Rhodophyta) in Santubong and Asajaya, Sarawak, Malaysia - Muhammad Nur Arif Othman,; Ruhana Hassan,; Mohd Nasarudin Harith,; Amir Shah Ruddin Md Sah, (Tropical Life Sciences Research, 2018)
Red seaweed Gracilaria, one of the largest genus in Division Rhodophyta inhabits Sarawak coastal water. This study was designed to identify the species of Gracilaria using morphological approach and to assess selected water quality parameters in Gracilaria habitats. Three field samplings were carried out in Santubong and Asajaya, Sarawak from November 2013 to December 2014. Overall, three species were identified namely Gracilaria changii, G. blodgettii and G. coronopifolia, attached to net of cage culture in Santubong and root of mangrove trees in Asajaya. In addition, three different taxa of aquatic macroinvertebrates (polychaete, small crab, bivalve) and single species of red seaweed (Acanthophora sp.) were observed in Gracilaria assemblages. An estimate of 37% to 40% of the upper part of the cage net in Santubong was covered by seaweeds and only 16% to 20% in Asajaya’s mangrove. The study had provided better information on identification of Gracilaria and their habitat in Sarawak. Future work involving DNA barcoding of each species is in progress. Rumput laut merah Gracilaria, salah satu genus terbesar bagi spesies Rhodophyta yang mendiami pesisir pantai Sarawak. Kajian ini dijalankan untuk mengenal pasti spesies Gracilaria menggunakan pendekatan morfologi dan untuk menilai parameter kualiti air terpilih dalam habitat Gracilaria. Tiga pensampelan lapangan dijalankan di Santubong dan Asajaya, Sarawak dari November 2013 hingga Disember 2014. Secara keseluruhannya, tiga spesies telah dikenal pasti iaitu Gracilaria changii, G. blodgettii dan G. coronopifolia, yang tersangkut pada jaringan sangkar di Santubong dan akar pokok bakau di Asajaya. Di samping itu, tiga jenis makroinvertebrata akuatik (polychaete, ketam kecil, dwicangkerang) dan spesies tunggal rumput laut merah (Acanthophora sp.) diperhatikan dalam himpunan Gracilaria. Anggaran 37% hingga 40% daripada bahagian atas sangkar di Santubong dilindungi oleh rumpai laut dan hanya 16% hingga 20% di bakau Asajaya. Kajian ini telah memberikan maklumat yang lebih baik mengenai pengenalan Gracilaria dan habitat mereka di Sarawak. Kajian masa depan yang membabitkan pengkodan DNA bagi setiap spesies juga sedang dijalankan.